CARVER+Shock and Business Process Management in Improving Food Safety of Primary Production - Aneta Wysokińska-Senkus; Justyna Górna; Magdalena Kaźmierczak; Paweł Mielcarek; Piotr Senkus (Agriculture, 2022)
Context: Food safety is essential for every human. It determines public health, nutrition, elimination of hunger, and the promotion of sustainable agriculture. It is crucial for sustainable production, consumption, and international food trade. Ensuring food safety is the fundamental challenge of the 21st century. Food safety is often related to food defense and includes protection against intentional contamination with various chemical, biological, or other harmful substances. By introducing food protection tools and methods, any company reduces risk and creates an opportunity to generate more significant and reliable profits and improved production for society. One such method could be the CARVER+Shock. The method is an offensive targeting prioritization tool that has been adapted for use in the food sector. Objective: The article aims to present the experience of the first implementation of CARVER+Shock in a Polish primary production company, to improve the approach to food safety and food defense. Methods: The article is a case study. Descriptive analysis was performed to analyze legal acts and safety management standards in food defense. The authors used the CARVER+Shock expert method to estimate companies’ vulnerability. CARVER is an acronym for Criticality, Accessibility, Recoverability, Vulnerability, Effect, Recognizability. The visualization and risk analysis were made using business process management and business process modeling (VACD diagram) Results and conclusions: Primary production enterprise dealing with the cultivation and confectioning of the pre-treatment and sale of peeled onions for further processing purposes was examined. Five essential stages of the production process were assessed, and risks were assigned. Recognizability and criticality turned out to be the most crucial attribute of CARVER+Shock. Overall, the study showed that the company was not fully prepared for the threat posed by food terrorism. The organization did not have any procedures describing how to proceed during deliberate attacks. In addition, workers had low awareness of food defense throughout the food chain. Based on these conclusions, several detailed improvement actions were formulated. The results obtained from the pioneering application of the CARVER+Shock method for a Polish primary production company may constitute a benchmark for other sectors of the food industry, both domestically and abroad. Significance: The article describes the results of the first Polish attempts to use CARVER+Shock and business process management to improve the approach to food safety in a primary production enterprise.